Isolasi Flavonoid Dari Herba Sida Rhombifolia, Linn. - Junuarti Jubahar; Husnal Hayati; Krisyanella Krisyanella (STIFARM Padang, 2010)
Flavonoid compounds have been isolated from Sida rhombifolia, Linn herbs. One kilogram of the dried herbs produced 1,7339 g ( 0.17339 % ) congealed extract and 3.87 mg of flavonoid A. Flavonoid A was yellow in colour, amorph solid which was decomposed at 232-234º C. Based on ultraviolet and infrared data and product of its hydrolysis, compound A was Flavonol-3-O-Galaktose.